Research on changes of the quality indicators of semi-finished products during during storage - N. Holembovska (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького. Серія: Харчові технології, 2021)
Considering the results of literary studies on the nutritional value and biological efficiency of cranberries and goji berries, it has been established that the development of the technology of semi-finished minced products with their use is relevant and has practical importance in the production of fish products. The article deals with the results of the chemical composition, organoleptic evaluation, and physical and chemical changes in semi-finished minced products with the addition of non-traditional raw materials and the establishment of their shelf life. The expediency of combining freshwater fish with plant material to expand the range of biologically valuable food products is presented in the article. The general positive impressions, harmonious, fish and sweet-salty taste, have shown the expediency of combining cranberries and goji berries with freshwater fish, as evidenced by high levels of appearance, taste, and smell. In terms of consistency, fish cutlets are plastic and dense on the cut. It has been found that there are processes of hydrolytic damage in the control sample after 90 days of storage, which indicates the intensive lipid hydrolysis and the accumulation of free fatty acids in these samples. In experimental samples, hydrolytic damage gradually increases and reaches its critical point only close to the end of the shelf life. Oxidation processes in the lipids of semi-finished products were studied by changes in the accumulation of primary oxidation products – peroxides and secondary products – carbonyl compounds. According to the dynamics of changes in the peroxide value of lipids of semi-finished products, it has been established that the control sample for 60-135 days has not been subjected to storage, and in experimental samples after 135 days, the quality of the fat deteriorates and is characterized as the one that is not subjected to storage. The research has established that the use of non-traditional raw materials in the production of semi-finished minced products allows to improve the technology of production and solve the problem of obtaining the product of a high nutritional value. The authors found that the developed technology of production of semi-finished fish products will significantly expand the range of products of functional purpose based on natural components, which will allow, to some extent, to broaden the current problem of processing raw materials from domestic reservoirs in Ukraine.